GOVERNMENT PERFORMANCE ACCOUNTABILITY (Case Study of the Ministry of Law and Human Rights Banten) - Bhanu, Bhanu Sachio; Jumiati, Ipah Ema; Aulia, Maya Siti; Adriani, Maylaffaiza Intan; Nazhifa, Annasya; Almaida, Salwa Syifa (The World of Public Administration Journal, 2023)
ABSTRACT Accountability is a form of accountability of a business owner or an organization to parties who are entitled to obtain and ask for information about business activities or performance in carrying out duties to achieve certain goals.Ã‚Â  Performance Accountability is the obligation of a government agency in accounting for the success or failure of the implementation of programs and activities. Performance Accountability is intended as from stakeholders to achieve the organization's mission measurably with predetermined performance targets / targets then outlined in government agency performance reports that are prepared periodically. The research method used is a literature review which refers to scientific journal articles as the source of the data. Accountability of government performance at the regional office of the Ministry of Law and Human Rights in Banten achieved success in 2022. The success is that the percentage of achievement of the Banten Regional Office performance indicators in 2022 is 110.49%, where there are 55 performance indicators that have succeeded in even exceeding the set target and there are 2 performance indicators. Meanwhile, for the analysis of resource efficiency in terms of performance indicator achievement, the overall average achievement of 58 performance indicators of the Banten Regional Office in 2022 reached 110.49%. This shows that there is an efficient use of resources in achieving performance in 2022, namely with the realization of the budget used in the implementation of performance of 96.88% can produce performance target achievements. Keywords : Accountability, Performance, Banten